Answer:
Value of X = 1
Value of y = 3
Solution,
Using substitution method,
y + x = 4
Move 'x' to the left hand side and change its sign:
y = 4 - x --------> equation (i)
Now,
2y - X = 5
putting the value of y from equation (i)
2( 4 - x ) - X = 5
8 - 2x - x = 5
8 - 3x = 5
- 3x = 5 - 8
- 3x = - 3
The difference sign (-) will be cancelled in both sides
3x = 3
3x/3 = 3/3
X = 1
Value of X is 1
Now, replacing the value of X in equation (i)
y = 4 - x
= 4 - 1
= 3
Value of y is 3
Hope this helps...
Good luck on your assignment...